Evaluation of decompressive craniectomy in mice after severe traumatic brain injury - Liu, Yuheng; Liu, Xuanhui; Chen, Zhijuan; Wang, Yuanzhi; Li, Jing; Gong, Junjie; He, Anqi; Zhao, Mingyu; Yang, Chen; Yang, Weidong; Wang, Zengguang (Frontiers in Neurology, 2022)
Decompressive craniectomy（DC） is of great significance for relieving acute intracranial hypertension and saving lives after Traumatic brain injury (TBI). In this study, the severe TBI mouse model was accomplished by electronically controlled cortical impact (CCI) and a surgical model of decompressive craniectomy was established. Further, a series of neurological function assessments were performed to better understand the pathophysiological changes after decompression. In this study, mice were randomly divided into three groups: TBI group, TBI+DC group, and Sham group. The mice in the TBI group and TBI+DC group received CCI after opening the bone window, after brain injury immediately returned the bone window to simulate the condition of the skull after a traumatic brain injury. The TBI+DC group received a craniectomy and tissue removal six hours after CCI. The mice in the TBI group received the same anesthesia process but no further treatment was done on the bone window and trauma. The mice in the Sham group received anesthesia and the process of opening the skin and bone window, but did not receive the CCI. Changes in Modified Neurological Severity Score, Rotarod, Morris water maze, intracranial pressure (ICP), cerebral blood flow（CBF）, brain edema, blood-brain barrier (BBB) damage, inflammatory factors, neuronal apoptosis, and glial cell proliferation were evaluated. Compared with TBI group, the ICP of the TBI+DC group was significantly lower, the neurological function and motor function at 24 h after injury significantly better, and the BBB damage after injury lighter. Most of the inflammatory cytokine expression and the number of apoptotic cells in the brain tissue of mice in the TBI+DC group were lower than in the TBI group at 3 days after injury, and with markedly reduced astrocyte and microglia proliferation. However, the degree of brain edema in TBI+DC mice was greater than in TBI group, and the neurological and motor functions, as well as the spatial cognitive and learning ability, significantly worse at 14 days after injury.